Self-Control Effects on Online Game Addiction Behavior among Senior High School Students - Najla Bintang Kamila; Dini Rakhmawati; Suhendri Suhendri; Najla Bintang Kamila; Dini Rakhmawati; Suhendri (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to analyze the influence of self-control on online gaming addiction behavior among high school students. The study employs a quantitative approach with a causal-associative design, utilizing a survey method and simple linear regression analysis. The sample consisted of 95 eleventh-grade students selected using a proportionate stratified random sampling technique from a population of 125 students. Data were collected using a Likert-scale questionnaire measuring the variables of self-control and online gaming addiction and were analyzed using SPSS. The results indicate a fairly strong relationship between self-control and online gaming addiction, with a correlation coefficient of 0.583 and a contribution of 34%. The resulting regression model was significant. The findings indicate that self-control has a positive and significant influence on online game addiction, suggesting that the higher the self-control, the higher the tendency toward online game addiction among the respondents. These results suggest that the relationship between self-control and online gaming addiction is not always negative but can be influenced by contextual factors such as gaming motivation and individual behavioral management patterns. This study implies that proper management of gaming behavior, as well as the development of self-regulation skills and digital literacy, need to be strengthened to minimize the negative impacts of online gaming addiction.